Yield stability in rice (Oryza sativa)-wheat (Triticum aestivum) system under long-term fertilizer use - KATYAL, V; GANGWAR, K S; GANGWAR, B (The Indian Journal of Agricultural Sciences, 2013)
Field trials werc conducted during 1978-79 to 1988-89 at Palampur and 1977-78 to 1994-95 at Pantnagar while atR S Pura from 1981-82 to 1994-95 to study the long-term effect of inorganic fertilizer application on yield sustainabilityand soil fertility in rice-wheal cropping system. The results showed that the system's productivity could be stable overyears with the application of 40-80-40 kg NPK/ha at Palampur. 80-40-40 kg NPK/ha at R S Pura and 120-40-40 kg NPK/ha at Pantnagar. The soil fertility build-up was not observed at any of the sites with the application of NPK due to continuous cropping of rice (Oryza saliva L.) - wheat (Triticum aestivum L. emend. Fiori & Paol.) sequence except at Palampur and Pantnagar where increase in available phosphorus was noticed over the initial soil status.